Investigations on the behavioral analysis of unbalanced synchronous generators - Kouchih, Djilali; Hachelaf, Redouane; Tadjine, Mohamed; Boucherit, Mohamed Seghir (Institute of Advanced Engineering and Science, 2024)
This paper describes a new methodology for the modeling and analysis of three-phase synchronous generators operating under an unbalanced regime. For this, an improved state model has been developed in order to determine significant signatures on stator and rotor electromagnetic quantities. This methodology is characterized by some advantages. Firstly, it can be generalized for the modeling of severe defects like open-phase and short circuits. Furthermore, by comparison to classical approaches based on the finite elements and symmetrical components methods, this approach gives a good compromise between precision and simulation time. The obtained results show the effectiveness of this approach for the analysis of unbalanced synchronous generators.